Growth and Nickel Absorption of Green Mustard (Brassica rapa L.) on Nickel-Contaminated Soil - Netty Syam (JURNAL GALUNG TROPIKA, 2022)
The waste generated by the nickel mining business has the potential to reduce soil fertility, causing plants not to grow normally and produce optimally. In fact, due to the high Ni content in the soil, it will be absorbed by the plants so that it cannot be used as food. The study aimed to determine the growth and absorption of nickel in mustard greens by applying compost and liquid fertilizer to nickel-polluted soil. The study used a randomized block design (RAK) with liquid fertilizer (PC) and compost application. The treatment consisted of (1) control (no PC + no compost); (2) Without PC+ compost 15 tonnes/ha; (3) Without PC + compost 20 tonnes/ha; (4) Without PC+25 tons/ ha; (5) PC 10 ml/liter + No compost; (6) PC 10 ml/liter + compost 15 tons/ha; (7) PC 10 ml/liter + compost 20 tons/ha; (8) PC 10 ml/liter + compost 25 tons/ha, which was repeated 3 times and consisted of 3 plants in each treatment. Data were analyzed using ANOVA and further testing with BNJ Test 0.05. The results showed that mustard plants on nickel-contaminated soil could grow normally and without poisoning symptoms. The application of 4 liters/ha of liquid fertilizer and 25 tons/ha of compost produced a higher number of leaves and fresh weight of mustard plants and were significantly different from other treatments. Mustard plants can absorb and accumulate nickel in the roots and leaves in the range of 425-455 mg/kg plant dry weight. Using green mustard plants in remediating land contaminated with heavy metals, especially nickel, can be an alternative by adding compost and liquid fertilizer to increase the biomass of mustard plants. However, it still has to be appropriately monitored, and the plants produced are not recommended for consumption.